2013
DOI: 10.1148/radiol.12121027
|View full text |Cite
|
Sign up to set email alerts
|

Integrating MR Imaging into the Clinical Workup of Pregnant Patients Suspected of Having Appendicitis Is Associated with a Lower Negative Laparotomy Rate: Single-Institution Study

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12121027/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 25 publications
2
19
0
3
Order By: Relevance
“…In this meta-analysis, indeterminate results (in which the appendix was not visualized and there was no peri-cecal fat stranding) were interpreted as negative results for the purposes of calculating performance characteristics [4]. In another report, the routine use of MRI in a single institution decreased the NA by 47% without significantly changing the perforation rate [11]. In Washington State, SCOAP data suggest that MRI is being increasingly utilized in the evaluation of pregnant women for possible appendicitis, as nearly one-third of pregnant patients in the database underwent MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, indeterminate results (in which the appendix was not visualized and there was no peri-cecal fat stranding) were interpreted as negative results for the purposes of calculating performance characteristics [4]. In another report, the routine use of MRI in a single institution decreased the NA by 47% without significantly changing the perforation rate [11]. In Washington State, SCOAP data suggest that MRI is being increasingly utilized in the evaluation of pregnant women for possible appendicitis, as nearly one-third of pregnant patients in the database underwent MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI provides a valuable tool for evaluation of pregnant patients with right lower abdominal quadrant pain due to features such as lack of ionizing radiation, the excellent safety profile, the exceptional characterization of pathologic tissue, and the capability of direct multiplanar cross-sectional imaging [10,12,14]. Moreover, MRI provides a systemic evaluation of the abdomen and/or pelvis, which enables identifying appendicitis as well as numerous other diagnoses [18]. MRI has a reported sensitivity of 80%e100% [5,15,18] and has the major diagnostic strength of being highly specific (93%e100% [5,15,18]).…”
Section: Tablementioning
confidence: 99%
“…Moreover, MRI provides a systemic evaluation of the abdomen and/or pelvis, which enables identifying appendicitis as well as numerous other diagnoses [18]. MRI has a reported sensitivity of 80%e100% [5,15,18] and has the major diagnostic strength of being highly specific (93%e100% [5,15,18]). In comparison to ultrasonography, MRI visualizes a higher percentage of appendices (52%e66.7% [13,15] versus 3%e12% [13,15]) Rapp et al [18] concluded that the routine incorporation of MRI into the clinical workup for suspicion of appendicitis in pregnant patients was associated with a decrease in the negative appendectomy rate of 47% without a significant change in perforation rate.…”
Section: Tablementioning
confidence: 99%
“…Few studies have demonstrated the effect of MRI on NLR, though its accuracy for diagnosing appendicitis has been shown to be similar to CT (1416). One center found that the NLR for pregnant women dropped from 55% to 29% when MRI was introduced into the diagnostic pathway (17). …”
Section: Introductionmentioning
confidence: 99%